An adenine/thymidine-rich region is integral to RepL-mediated DNA replication - Huan, Yang Wei; Brown, Russell; Wang, Baojun (Frontiers in Microbiology, 2023)
The lytic replication of bacteriophage P1 requires RepL expression and the lytic stage origin, oriL, which is postulated to be located within repL gene sequence. The exact sequence of P1 oriL and the mechanism(s) of RepL-mediated DNA replication, however, are not fully understood. By using repL gene expression to induce DNA replication of a gfp and a rfp reporter plasmids, we demonstrated that synonymous base substitution in an adenine/thymidine-rich region of repL gene sequence, termed AT2, significantly inhibited the RepL-mediated signal amplification. Contrastingly, mutations in an IHF and two DnaA binding sites did not affect the RepL-mediated signal amplification significantly. A truncated repL sequence with the AT2 region allowed RepL-mediated signal amplification in trans therefore verifying a significant role of the AT2 region in RepL-mediated DNA replication. A combination of repL gene expression and a non-protein-coding copy of repL gene sequence (termed nc-repL) was able to amplify the output of an arsenic biosensor. Furthermore, mutation(s) at single or multiple positions within the AT2 region produced varying levels of RepL-mediated signal amplification. Overall, our results provide novel insights into the identity and location of P1 oriL as well as demonstrating the potential of using repL constructs to amplify and modulate the output of genetic biosensors.